STRATEGI PENDIDIKAN DASAR UNTUK MENCAPAI AKUNTABILITAS PENGELOLAAN PENDIDIKAN - mahmudah, siti; Yoenanto, Nono Hery (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2023)
Good education financing accountability will produce quality education output. Accountability must be applied in every aspect of financing to support activities, because cost is one of the most influential elements in an educational activity. This literature reviu aims to determine strategies in the management of basic education accountability. Data collection is based on a literature study of 7 literatures ranging from 2013 to 2020. The articles were obtained by reviuing the official Google Scholar website. The results of the study indicate that the strategies that can be carried out by a basic education organization to achieve education management accountability. Good governance, wealth management, school-based management (SBM), and principal competencies.